Adsorption Of Methyl Violet From Aqueous Solution By Using Activated Carbon From Mangrove Timber Via Physiochemical Method - Abdul Rahman, Nawal Auni (Universiti Sains Malaysia, 2018)
Activated carbon is commonly used to trap toxins and chemicals. It is made from a variety of sources. In the past studies, it has been found that the production of activated carbon from agriculture waste is one of the most environment-friendly which transform waste into a valuable product. Thus, the objective of this project was to prepare activated carbons from mangrove timber using physiochemical method. The activated carbon were characterized by Thermogravimetric Analyzer, Brunauer-Emmett-Teller and Elemental Analyzer. The methyl violet adsorption of the prepared carbons were evaluated. The different factors affecting adsorption of methyl violet (MV) were studied which are the activation temperature (650℃, 750℃ and 850℃) and KOH impregnation ratio (1, 1.5 and 2). The highest methyl violet removal was obtained at activated carbon with parameter 850℃ of activation temperature and 1.0 of KOH impregnation ratio. It was observed that AC850(1) gives the highest surface area of 852.1913 m3 /g and total volume pore of 0.44 cm3 /g. The maximum removal percentage were determined at 100 mg/L initial methyl violet concentration at 87.81 %. The adsorption of methyl violet on mangrove based activated carbon was found to follow the Freundlich adsorption isotherm and pseudo second order kinetic model. The result of adsorption study showed that the activated carbon prepared from mangrove timber is a suitable adsorbent for methyl violet removal from aqueous solution.